On the role of Pd β-hydride in the reduction of nitrate over Pd based catalyst - Mendez, Claudio Matias (2008)
Two monometallic palladium catalysts supported on γ-Al2O3 were synthesized using different precursors, Pd(AcAc)2 and Pd(NO3)2, while Pd-Cu/γ Al2O3 catalysts were prepared from those parent catalysts. The samples were tested for the elimination of nitrate and nitrite from aqueous solutions using hydrogen as a reductant in a standard batch reactor. Besides, the reduction of nitrate was carried out in a series of two reactors by an electrochemical cell mechanism. In this case, nitrate was reduced to nitrite by electrons supplied from the first reactor. The following reduction of nitrite was performed over the monometallic catalyst. Both the conversion and the selectivity to N2 were higher than in the standard batch reactor. Monometallic samples prepared from Pd(AcAc)2 showed an extremely high selectivity to the desired product. The catalysts were characterized by transmission electron microscopy (TEM), temperature programmed reduction (TPR) and H2 chemisorption. Differences in particle size and β-hydride formation were observed for the different samples. The possible role of Pd β-hydride in the formation of overhydrogenated products is discussed. © 2008 Elsevier B.V. All rights reserved.